The Seller's Side of the Story: Acquisition as Courtship and Governance as Syndicate in Entrepreneurial Firms - Graebner, Melissa E.; Eisenhardt, Kathleen M. (Administrative Science Quarterly, 2004)
In contrast to the prior acquisitions literature, which has emphasized the buyer's perspective, we examine the seller's perspective. This has important implications for understanding both the acquisition process and, more broadly, corporate governance in successful firms. Using a multiple-case, inductive study of 12 technology-based ventures, we find that acquisition occurs when sellers are pushed toward acquisition by difficult, albeit natural strategic hurdles, such as a chief executive search or funding round, and by strong personal motivations for sale, such as past failures and investments by friends. Sellers are also more likely to be pulled toward acquisition by attractive buyers that offer synergistic combination potential and organizational rapport, factors usually associated with the long-term interests of buyers. We reframe acquisition as courtship and corporate governance as a syndicate, indicating joint decision making with some common goals, and explore the generalizability of these views for private versus public firms and other contingencies. Together, courtship and syndicate suggest a behaviorally informed account of organization that belies the rhetoric of price and self-interest.